Uma casa de gerações - Projecto de uma casa de férias em Vila Nova de Cerveira - Margarida Maria Norton Sousa Rosa (2018)
The purpose of this dissertation is to present an architectural and academic project aiming to approach reality. This project is a transition from an academic research to a project that could see the light of day. The project is taking place in Vila Nova de Cerveira, Portugal. The features of the house that had to be taken into account are the fact that it is a holiday house of a family of three who always had thought of the next generations. Therefore one of the most important aspects was to balance and take into account the present and future generations in order to meet all requirements. Throughout the dissertation, we will understand the different steps and methods that have been used in order to fit all the features and requirements. To the exchange of ideas between the client and myself, confronting personal motives and impulses to the conditions that have been put and taking into account the topography, through the constraints of legislative and normative scope. All this without putting on the side the constant evolution and development of the work carried out in the different phases. All in all, this dissertation illustrates the culmination of an academic work project leading to the preparation of a real life concept. The main purpose being to get prepared to practice architecture in a real life environment.